Young bone marrow transplantation prevents aging‐related muscle atrophy in a senescence‐accelerated mouse prone 10 model. Issue 6 (4th September 2022) - Inoue, Aiko; Piao, Limei; Yue, Xueling; Huang, Zhe; Hu, Lina; Wu, Hongxian; Meng, Xiangkun; Xu, Wenhu; Yu, Chenglin; Sasaki, Takeshi; Itakura, Kohji; Umegaki, Hiroyuki; et al.
Abstract: Background: Young bone marrow transplantation (YBMT) has been shown to stimulate vascular regeneration in pathological conditions, including ageing. Here, we investigated the benefits and mechanisms of the preventive effects of YBMT on loss of muscle mass and function in a senescence‐associated mouse prone 10 (SAMP10) model, with a special focus on the role of growth differentiation factor 11 (GDF‐11). Methods: Nine‐week‐old male SAMP10 mice were randomly assigned to a non‐YBMT group ( n  = 6) and a YBMT group ( n  = 7) that received the bone marrow of 8‐week‐old C57BL/6 mice. Results: Compared to the non‐YBMT mice, the YBMT mice showed the following significant increases (all P < 0.05 in 6–7 mice): endurance capacity (>61.3%); grip strength (>37.9%), percentage of slow myosin heavy chain fibres (>14.9–15.9%). The YBMT also increased the amounts of proteins or mRNAs for insulin receptor substrate 1, p‐Akt, p‐extracellular signal‐regulated protein kinase1/2, p‐mammalian target of rapamycin, Bcl‐2, peroxisom proliferator‐activated receptor‐γ coactivator (PGC‐1α), plus cytochrome c oxidase IV and the numbers of proliferating cells (n = 5–7, P < 0.05) and CD34+/integrin‐α7+ muscle stem cells (n = 5–6, P < 0.05). The YMBT significantly decreased the levels of gp91phox, caspase‐9 proteins and apoptotic cells (n = 5–7, P < 0.05) in both muscles; these beneficial changes were diminished by the blocking of GDF‐11 (n = 5–6, P < 0.05). An administration of mouse recombinant GDF‐11 improved the YBMT‐mediated muscle benefits (n = 5–6, P < 0.05). Cell therapy with young bone marrow from green fluorescent protein (GFP) transgenic mice exhibited GFP+ myofibres in aged muscle tissues. Conclusions: These findings suggest that YBMT can prevent muscle wasting and dysfunction by mitigating apoptosis and proliferation via a modulation of GDF‐11 signalling and mitochondrial dysfunction in SAMP10 mice.